Ville e residenze extraurbane del Quattrocento a Palermo e in Sicilia - Nobile, Marco Rosario (Opus Incertum, 2016)
With the exception of a few splendid residences inherited from the past and related to the Norman or Swabian courts -which areboth in use and fully operative- the documented cases of new constructions in the 15th century are rare. In a city such as Palermo,the great private gardens were internal to the walled circuit, which allowed for an elitist way of life and matching social behaviours.A compact group of towered buildings constructed during that century in several places throughout the island constitutes, however,a significant phenomenon. In these buildings, which were commissioned by distinguished clients (the Cabrera in Pozzallo, theVentimiglia in Monteleone, the Speciale in Ficarazzi), a blend can be identified between defensive needs, productive interests,or else connected to hunting, and architectural and distributive choices which reflect conventions that are common to the entireMediterranean basin, but also the influence of the Aragonese court and that of the buildings favoured by the monarchy.